Analisis Kinerja Pegawai dilihat dari motivasi dan disiplin pada Dinas Perindustrian dan Perdagangan Kabupaten Malang - Ubaidillah Fauzi; RM Mahrus Alie (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2022)
Improving employee performance is one of the efforts made by every company or organization to achieve a goal. In a company there are factors to improve performance, one of which is work motivation and work discipline. This study aims to determine and analyze: (1) the effect of work motivation on employee performance, (2) the effect of work discipline on employee performance and (3) the effect of work motivation and work discipline on employee performance. This research was conducted at the Department of Industry and Trade of Malang Regency. This research is a quantitative study using the SPSS version 23 data processing program. The sample in this study was 56 employees. In analyzing the data using descriptive analysis method, multiple linear regression analysis, using the t test and F test. The results showed that partially or simultaneously work motivation and work discipline affect employee performance. In the test results of the coefficient of determination (R2) a value of 0.548 is obtained. This shows that the magnitude of the influence of work motivation and work discipline is 54.8%.